Clinical Performance of Oxgall Pre-enrichment qPCR for Salmonella Detection in Antibiotic-Exposed Patients Suspected of Typhoid Fever - Annisa Pratiwi Gunawan; Sartika Rajagukguk; Yusuf Hanafiah; Aurellia Firstania; Muhammad Fathurrahman; Eka Yuni Nur Jannah; Putri Ayu Lestari (Rifa'Institute, 2026)
Introduction: The reliability of typhoid fever diagnostics in endemic regions is frequently compromised by low circulating bacterial loads and widespread pre-hospital antibiotic use. Objective: This study evaluates the specific factors contributing to false-negative outcomes when using an oxgall-pre-cultured real-time polymerase chain reaction method for Salmonella typhi detection. Method: A cross-sectional evaluative study was conducted using thirty blood samples from Widal-positive patients. Laboratory optimization using spiked samples established a technical limit of detection. Clinical specimens were analyzed using conventional blood culture and real-time polymerase chain reaction targeting the invA gene after a six-hour enrichment in ten percent oxgall medium. Result and Discussion: While laboratory optimization successfully detected spiked matrices, one hundred percent of clinical samples yielded negative results via real-time polymerase chain reaction, and blood culture identified only one positive case. Evaluative analysis revealed that all subjects received antibiotic therapy prior to sampling and most were already in the second week of fever, exceeding eight days. Conclusions: The high rate of false-negative results is primarily due to bacterial loads dropping below the limit of detection because of antibiotic interference and late-stage sampling. Furthermore, ten percent oxgall concentration may inhibit the recovery of antibiotic-stressed bacteria